Identification of the miRNA–mRNA regulatory network in a mouse model of early fracture - Wang, Maochun; Xie, Zhiyang; Yan, Kaili; Qiao, Chongxu; Yan, Shunchao; Wu, Guoping (Frontiers in Genetics, 2024)
Fracture healing is a complex process which involves multiple molecular events and the regulation mechanism is not fully understood. We acquired miRNA and mRNA transcriptomes of mouse fractures from GEO database (GSE76197 and GSE192542), and integrated the differentially expressed miRNAs and genes between control and fracture to construct regulatory networks. There were 130 differentially expressed miRNAs and 4819 differentially expressed genes, including 72 up-regulated and 58 down-regulated miRNAs, along with 2855 up-regulated and 1964 down-regulated genes during early fracture healing. Gene ontology analysis revealed that most of differentially expressed genes were enriched in extracellular matrix organization and extracellular structure organization. And KEGG enrichment suggested cell cycle, DNA replication and mismatch repair were involved in the progression of fracture healing.Furthermore, we constructed a molecular network of miRNAs and mRNAs with inverse expression patterns to elucidate the molecular basis of miRNA-mRNA regulation in fracture. The regulatory network highlighted the potential targets which may help to provide a mechanistic basis for therapies to improve fracture patient outcomes.